“Bem vido au iferno”: vidas, mortes e resistências no Sistema Socioeducativo do Ceará (2006-2022) - Araújo, Francimara Carneiro de (2023)
This work aims to describe and analyze the events and processes of a crisis in the juvenile justice System of Ceará, in order to propose a critical sociological interpretation of the lives and right to exist of adolescents from the underprivileged classes in a Brazilian Northeastern State. For this, I start from the analysis of detention centers and how a punitive mechanism was historically created, which despite being transfigured into “educational”, always gave rise to the control of deviant childhoods. I take the period from 2006 to 2022 as a time reference for this analysis. This time frame precedes the peak period of the crisis and also includes its subsequent period, as a mean s of understanding its impacts and developments. The issues that guide the production of knowledge in this work are linked to social, cultural, legal and political conflicts that make the childhood and adolescence of sons and daughters of black mothers, wo rking classes and residents of urban peripheries a target of attacks that negatively affect the construction of their social relationships and sense of belonging. From a methodological point of view, this research was built from my social engagement in chi ldhood causes, relying on autoethnography as a possibility of interpreting field data that were also collected through reflective and engaged observation, documentary research, interviews and focus group. The thesis seeks an intersectional theoretical appr oach, understanding that race structures class in Brazil and that the debate about women's oppression forms a tripod: women, r ace and class , which in the discussion about incarceration presents itself as “hierarchies of oppression” that determine who will or will not be de prived of liberty . The thesis is also based on debates around the social history of childhood, the sociology of punishment, the sociology of rebellions, the sociology of prisons and the discussion around new criminal groups called factions , pleading, in the end, for a Sociology of Childhood "found in prison" in which, from a structural change in the paradigms that base the incarceration of children and adolescents, the primacy of life and not that of death prevails. Keywords: